Factors related to the Perception of Acupressure as Prevention of Anemia in the Elderly at the Nursing Home - Imrok Atus Sholihah; Titik Haryanti; Nur Ani (Masters Program in Public Health, 2023)
Background: Anemia or known by the public as anemia in the elderly often occurs unknowingly. The prevalence of anemia in Indonesia in the elderly is 42.3%. Acupressure utilizes stimulation on the body's acupuncture points, ears and scalp to affect the flow of the body's bioenergy called qi as one of traditional medicine. Perceptions of the use of traditional medicine are of three types: holding belief in conventional medicine, doubting conventional medicine, and holding belief in both traditional medicine and conventional medicine. The purpose of this study was to determine the factors associated with the perception of acupressure as a prevention of anemia in the elderly at nursing homes.Subjects dan Method: This study was a cross-sectional study in January 2023. The sample used was 110 elderly people in nursing homes in the Surakarta area, selected using a purposive random sampling technique. The dependent variable of this research is the perception of acupressure as prevention of anemia. The independent variables in this study were education of the elderly, knowledge of acupressure, history of anemia, safety of acupressure and willingness to do acupressure. Data collected by questionnaire. Data analysis used multiple logistic regression with Stata 13.Results: Factors related to positive perceptions of acupressure as prevention of anemia in the elderly were higher education in the elderly (OR= 12.77; 95% CI= 1.842 to 88.74; p=0.010), high knowledge about acupressure (OR= 13.05; 95% CI= 2.22 to 76.78; p=0.004), had a history of anemia (OR= 13.50; 95% CI= 2.15 to 84.59; p=0.005), safety of acupressure (OR= 32.85; 95% CI= 4.96 to 217.55; p<0.001), and willingness performed acupressure (OR= 11.03; 95% CI= 1.97 to 61.71; p=0.006).Conclusion: Factors related to the perception of acupressure as prevention of anemia in the elderly are the elderly's higher education, high knowledge of acupressure, history of anemia, safety of acupressure, and willingness to do acupressure. Keywords: perception of acupressure, prevention of anemia, the elderly. Correspondence: Imrok Atus Sholihah. Public Health, Universitas Veteran Bangun Nusantara Sukoharjo. Jl. Letjend Sujono Humardani No. 1, Sukoharjo, Central Java, Indonesia. Email: imrokatussholihah6@gmail.com. Mobile: +6281225210252.